Low velocity impact response of 3D printed structures formed by cellular metamaterials and stiffening plates: PLA vs. PETg. (15th January 2021) - Santos, F.A.; Rebelo, H.; Coutinho, M.; Sutherland, L.S.; Cismasiu, C.; Farina, I.; Fraternali, F.
Abstract: This work studies the low-velocity impact response of 3D-printed layered structures made of thermoplastic materials (PLA and PETg), which form sacrificial claddings for impact protection. The analyzed structures are composed of crushable cellular cores placed in between terminal stiffening plates. The cores tessellate either honeycomb hexagonal unit cells, or hexagonal cells with re-entrant corners, with the latter exhibiting auxetic response. The given results highlight that the examined PETg protectors exhibit higher energy dissipation ratios and lower restitution coefficients, as compared to PLA structures that have the same geometry. It is concluded that PETg qualifies as an useful material for the fabrication of effective impact protection gear through ordinary, low-cost 3D printers.